The farewell party [videorecording (DVD)] - Granit, Tal; Maymon, Sharon; Reṿaḥ, Zeʼev, 1940-; Rosen, Alisa, 1939-; Finkelstein, Levana (First Run Features, 2015)
Tackling an extremely sensitive issue in a vibrant, humorous way, this is the story of Yehezkel and his wife Levana. Well into their 70s, they are living contented lives inside a Jerusalem retirement home. But they are shocked when their dear friend Max falls prey to an irreversible illness. Looking to escape a slow, painful death, Max asks Yehezkel for help to end his suffering.